1251 Risk Stratification in the Management of Post-Tonsillectomy Haemorrhage. (12th October 2021) - Holden, P; Wilson, G; Daniel, M; Srivastava, R
Abstract: Aim: Tonsillectomy represents 17% of the elective workload in ENT and post-tonsillectomy haemorrhage is the most significant complication of this procedure. Accordingly, the GIRFT (Getting It Right First Time) report for ENT surgery focusses on the prevention of post-tonsillectomy bleeding. However, there is little guidance on the management of post-tonsillectomy haemorrhage. A local guideline for the management of post-tonsillectomy haemorrhage was introduced in 2020 based on expert consensus. This audit examines the management of patients readmitted with post-tonsillectomy haemorrhage in 2019 and compares this to the management suggested in the new guideline. Method: Patients readmitted with post-tonsillectomy haemorrhage within 30 days of a tonsillectomy performed in 2019 were identified. These were retrospectively stratified into risk categories according to both patient and clinical factors. Management was audited against the new guideline including both the initial patient assessment and the treatment suggested for their respective risk category. Results: Fifteen patients were identified and stratified into low, medium and high-risk categories. All patients in the "low risk" category were successfully treated conservatively. One patient from the "medium risk" category had a further bleed as an inpatient during the proposed period of observation in the new guideline and was thereafter treated as "high risk". Within the "high risk" category two patients required return to theatre for arrest of post-tonsillectomy haemorrhage. Conclusions: These results show that the risk stratification proposed in these guidelines may be useful in the management of post-tonsillectomy haemorrhage. Amendments to the guideline and a re-audit are in progress.